An epitope in the V1 domain of the simian immunodeficiency virus (SIV) gp120 protein is recognized by CD8+ cytotoxic T lymphocytes from an SIV-infected rhesus macaque. - Erickson, A L (1994)
Cytotoxic T-lymphocyte (CTL) responses against the external envelope glycoprotein (gp120) of the simian immunodeficiency virus (SIV) were studied in a rhesus macaque infected with SIVmac/239. CD8+ T cells enriched from concanavalin A-stimulated peripheral blood mononuclear cells lysed autologous target cells infected with recombinant vaccinia virus vectors expressing the SIVmac/239 or SIVsm/H4 envelope protein, which share approximately 80% identity in amino acid sequence. A CD8+ CTL line derived by limiting dilution culture of the concanavalin A-stimulated lymphocytes was also specific for the envelope proteins of both SIV isolates. Mapping studies revealed that this cell line recognized an epitope between amino acids 113 and 121 (CNKSETDRW) in the V1 domain of gp120. Amino acid substitutions are observed at positions 116 and 120 among viruses of the SIVsm/mac/human immunodeficiency virus type 2 group, and thus synthetic peptides representing these variants were tested for the ability to sensitize target cells for lysis by the CTL line. Autologous target cells sensitized with a synthetic peptide representing the SIVmac/239 sequence were efficiently killed. In contrast, recognition of target cells was reduced or abolished when peptides representing the amino acid substitutions at position 116 or 120 of other SIVmac, SIVsm, SIVmne, or SIVstm strains were tested. Further studies of CTL responses against this epitope could provide insights into mechanisms of variability within the gp120 V1 domain and its importance in evasion of immunity in infected or vaccinated monkeys.